LAYANAN TANPA TURUN SERPONG - Peter Lay; Martin Halim (Jurusan Arsitektur dan Perencanaan, 2021)
According to Martin Heidegger, dwelling is an individual activity on this earth. Shopping is one of important activity for surviving. In early 2020, COVID-19 occurred so that the government issued a policy to carry out social distancing. The policy damages the dwelling activities that occur. In general, every individual must maintain a distance but this is often violated. Vehicles can solve this problem where each individual is forced to make a distance. The site was chosen based on Jalan Raya Serpong, where it connects South Tanggerang and Bogor. The site was chosen close to the entrance of Alam Sutera because the designation was predominantly residential. More road users on the site use vehicles while pedestrians are minimal. The lack of pedestrians is due to poor public facilities. After the government issued a policy for social distancing, the public preferred to use the drive-thru facility for shopping. So that the design uses the concept of service without going down. The service without getting down here talks about 3 things, namely drive-in, drive-thru, and pickup point. Where the main programs are dine-in and drive-thru supermarkets. With the concept dwelling activity can still run. The concept is also not bound by time so that there is no expiration date because vehicles will always exist in the future. The project aims to maintain the existing lifestyle. Keywords: Dwelling; Lifestyle; Service without going down; Social Distancing; Transportation. AbstrakMenurut Martin Heidegger dwelling adalah sebuah aktivitas individu di dalam bumi ini. Aktivitas manusia yang paling penting adalah berbelanja dimana berfungsi untuk memenuhi kebutuhan. Pada awal tahun 2020 COVID-19 terjadi sehingga pemerintah mengeluarkan kebijakan untuk melakukan social distancing. Kebijakan tersebut merusak kegiatan dwelling yang terjadi. Secara umum setiap individu harus menjaga jarak namun hal tersebut sering dilanggar. Kendaraan bermotor dapat menyelesaikan masalah tersebut dimana setiap individu dipaksa membuat jarak. Tapak dipilih berdasarkan Jalan Raya Serpong, dimana jalan tersebut menghubungi Tanggerang Selatan dan Bogor. Tapak terpilih dekat dengan entrance Alam Sutera karena peruntukkan lebih dominan hunian. Pengguna jalan pada tapak lebih banyak menggunakan kendaraan bermotor sedangkan pejalan kaki sangat minim. Kurangnya pejalan kaki diakibatkan fasilitas umum yang kurang baik. Setelah pemerintah mengeluarkan kebijakan untuk social distancing masyarakat lebih senang menggunakan fasilitas drive-thru untuk berbelanja. Sehingga dalam rancangan menggunakan konsep layanan tanpa turun. Layanan tanpa turun disini berbicara 3 hal yaitu drive-in, drive-thru, dan pickup point. Dimana program utama berupa dine-in dan drive-thru supermarket. Dengan adanya konsep layanan tanpa turun aktivitas dwelling masih dapat berjalan . Konsep tersebut juga tidak terikat dengan waktu sehingga tidak ada masa kadaluarsa karena kendaraan akan selalu ada di masa depan. Proyek tersebut bertujuan untuk mempertahankan gaya hidup yang ada.